The perceptions and experience of the diabetic person with an insulin pump: a review of the literature - Strini, Veronica; Schiavolin, Roberta; de Barbieri, Ilaria; Prendin, Angela (Acta Biomedica Atenei Parmensis, 2021)
Background: diabetes mellitus is a chronic disease of the endocrine system, characterized by an increase in the concentration of glucose in the blood. For patients with diabetes, it is possible to cover the need for insulin through the use of an insulin pump, a subcutaneous implantable device, which aims to simulate the action of the Langherans islets. Therapy with an insulin pump allows patients who use it to have a greater flexibility in the long-term management of diabetes. Objective: to investigate in the literature the perceptions and experiences of patients subjected to the use of the insulin pump. Methods: this review was carried out using the international databases Pubmed, CINAHL and COCHRANE. The mesh terms "Insulin infusion system, attitude to health, experiences, emotions, perceptions, activities of daily living" were used combined with the Boolean operator AND. Age limits and language were set and literature was investigated from 2008 to 2018, respecting specific inclusion and exclusion criteria. Results: 260 articles from the Pubmed database were analyzed, 26 articles from Cinhal, no articles by COCHRANE; of these 188 excluded based on the reading of the abstract and because they were duplicate articles, 7 because they did not meet the inclusion criteria. 15 articles were included in the review. Discussion: four main themes emerged regarding the personal experience of patients with insulin pumps: perceptions deriving from the use of the insulin pump, behaviour deriving from therapy, obstacles to adequate glycemic control and discrepancy between education received and reality. Conclusions: different moods and behaviors have been reported in people who use the insulin pump: one above all the fear of hypoglycemia. There are different expectations from patients and nurses. In addition to adequate training with respect to direct patient care, training is also required for nursing staff in emotional support and in technological development.